Bain type of X‐linked syndromic mental retardation in boys. Issue 6 (18th March 2019) - Harmsen, Stefani; Buchert, Rebecca; Mayatepek, Ertan; Haack, Tobias B.; Distelmaier, Felix
Abstract : A hemizygous variant in the HNRNPH2 gene causes MRXSB in a male individual.